2022
DOI: 10.36348/sijap.2022.v05i01.001
|View full text |Cite
|
Sign up to set email alerts
|

Aloe Vera Gel Effect on Skin and Pharmacological Properties

Abstract: Aloe Vera, a cactus-like plant belongs to Asphodelaceae (Liliaceae) family has been used for traditional medical purposes for thousands of years. Aloe Vera derives its name from the Arabic word “Alloeh” which means “shining bitter substance” because of the bitter liquid found in the leaves and Vera which means “true” in Latin. There are over 300 species of aloe, most of which are native to South Africa, Madagascar and Arabia. Aloe leaves can be separated into two basic products: the latex, a bitter yellow liqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…Aloe vera gel, extracts, juice, and powder have become popular and generally recognized as safe substances for applications in food, dietary supplements, and Ayurvedic drugs [19]. Several studies have demonstrated its anti-inflammatory, antibacterial, antioxidant, antiviral, anti-ulcer, wound healing, lipid-lowering, antidiabetic, antihypertensive, and immune regulator properties [19][20][21][22]. Studies on its chemical composition revealed that the main active phytoconstituents of A. vera are aloin, emodin, rhein, acemannan, Aloe emodin, mannose-6-phosphate, and aloesin [19], whose structures are depicted in Figure -1.…”
Section: Introductionmentioning
confidence: 99%
“…Aloe vera gel, extracts, juice, and powder have become popular and generally recognized as safe substances for applications in food, dietary supplements, and Ayurvedic drugs [19]. Several studies have demonstrated its anti-inflammatory, antibacterial, antioxidant, antiviral, anti-ulcer, wound healing, lipid-lowering, antidiabetic, antihypertensive, and immune regulator properties [19][20][21][22]. Studies on its chemical composition revealed that the main active phytoconstituents of A. vera are aloin, emodin, rhein, acemannan, Aloe emodin, mannose-6-phosphate, and aloesin [19], whose structures are depicted in Figure -1.…”
Section: Introductionmentioning
confidence: 99%
“…is native to the Arabian Peninsula and now cultivated in several warm climatic zones of world including Asia, America, and Europe (Grace et al 2015, Giannakoudakis et al 2018). The A. vera industry has expanded throughout the world and the mucilaginous gel from the parenchymatous cells in the inner leaf pulp is used in many products, including fresh gel, juice, and multiple formulations for health, medicinal, and cosmetic purposes (Saleem et al 2022). Its leaf extracts are rich in nutrients and contain over 200 active compounds including simple/complex polysaccharides, amino acids, proteins, enzymes, terpenoids, flavonoids, saponins, minerals, vitamins, phenols, and other metabolites, allowing a broad spectrum of medicinal applications (Saniasiaya et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that it may positively impact haematological parameters, including blood cells, which could be promising news for those suffering from blood-related conditions (Amber et al, 2021). It also contains anthraquinones, compounds that have been found to have antiinflammatory and antioxidant properties) Kumar et al, 2019;Nikookalam et al, 2019;Ebrahim et al, 2020;Saleem et al, 2022). This means that A. vera not only has the potential to heal and protect the body from disease, but it may also help reduce inflammation and promote overall health and wellness.…”
Section: Introductionmentioning
confidence: 99%